2019
DOI: 10.1111/jch.13535
|View full text |Cite
|
Sign up to set email alerts
|

Salt‐induced effects on microvascular function: A critical factor in hypertension mediated organ damage

Abstract: Salt has been linked very closely to the occurrence and complications of arterial hypertension. A large percentage of patients with essential hypertension are salt‐sensitive; that is, their blood pressure increases with increased salt intake and decreases with its reduction. For this reason, emphasis is placed on reducing salt intake to better regulate blood pressure. In day‐to‐day clinical practice this is viewed as mandatory for hypertensive patients who are judged to be salt‐sensitive. Previous studies have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 48 publications
2
21
0
4
Order By: Relevance
“…High sodium intake and increased BP levels are linked by changes in vascular resistances, but the mechanisms controlling this phenomenon may not be only viewed as a reflex pressor response aimed at increasing sodium excretion. Excessive salt intake may induce several adverse effects, causing microvascular endothelial inflammation, anatomic remodeling, and functional abnormalities, even in normotensive subjects [13]. More recent studies have shown that changes in sodium plasma levels do not only exert their effects on small resistance arteries, but may also affect the function and structure of large elastic arteries.…”
Section: Sodium Intake and Blood Pressure Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…High sodium intake and increased BP levels are linked by changes in vascular resistances, but the mechanisms controlling this phenomenon may not be only viewed as a reflex pressor response aimed at increasing sodium excretion. Excessive salt intake may induce several adverse effects, causing microvascular endothelial inflammation, anatomic remodeling, and functional abnormalities, even in normotensive subjects [13]. More recent studies have shown that changes in sodium plasma levels do not only exert their effects on small resistance arteries, but may also affect the function and structure of large elastic arteries.…”
Section: Sodium Intake and Blood Pressure Valuesmentioning
confidence: 99%
“…An increased salt intake may clearly provoke an expansion in circulating volumes, an increase in flow and BP values, and thus an adverse remodeling of arterial wall mediated by the mechanic load through shear stress and an increase in wall tension. Beyond that, several experimental and clinical studies have recently demonstrated the adverse effects of high sodium intake in the microvascular circulation [13].…”
Section: Salt-induced Vasodysfunctionmentioning
confidence: 99%
“…The greater “stiffness” of endothelial cells would lead to a reduction in the activity of nitric oxide synthase (eNOS) and an increase in vascular resistance, with a consequent increase in blood pressure [ 40 ]. This condition could, in turn, induce microvascular remodeling and a systemic proinflammatory state leading to microvascular endothelial inflammation, anatomical remodeling, and functional abnormalities, as shown in animal models [ 41 ]. The presence of a proinflammatory state involving the endothelium due to an excessive intake of salt has been demonstrated in several studies performed on rodents [ 42 , 43 , 44 ] and on humans [ 45 , 46 ].…”
Section: Salt and Pathogenesis Of Arterial Hypertensionmentioning
confidence: 99%
“…At 7 weeks of age, the HS group and GZD group were fed with high-salt (8% NaCl) diet progressively developed hypertension. Five weeks after 8% NaCl diet, the mean value of the SBP ≥ 180 mmHg indicated that the model of salt-sensitive hypertension was established successfully according to previous studies [9,11,23,24]. At 12 weeks of age, the NS group and HS group were fed with physiological saline at 2 mL/day, while 2 mL/4.0 g of GZD crude drug/kg/day was administered to the GZD group according to the results of a previous study [11].…”
Section: Preparation Of Guizhi Decoction and Interventionmentioning
confidence: 99%
“…According to the TCM therapeutic theory of “regulating Ying-Wei in case of heart damage”, we identified an association between the dysfunction of Ying-Wei and hypertension-related pathological characteristics. TCM pathophysiology and experimental evidence indicate that Spleen and Kidney Yang Deficiency syndrome is the main TCM syndrome related to salt-sensitive hypertension and the main pathological feature of hypertensive Ying-Wei disharmony [ 9 11 ]. Guizhi decoction (GZD) is a classical TCM prescription for the treatment of Ying-Wei disharmony and Yin and Yang imbalance [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%